1998
DOI: 10.1021/cm9802797
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of YMnO3 in a Perovskite Structure as a Thin Film

Abstract: Using pulsed laser deposition (PLD), metastable perovskite YMnO3 films were grown from a hexagonal YMnO3 target. The stabilization of the metastable phase is a result of the structural similarity between it and the perovskite substrates. X-ray and electron diffraction confirm the films' epitaxial nature but evince that the orientation and residual strains depend on the substrate. The implication of these findings is that PLD is a simple synthetic approach to stabilizing new, more complex, metastable perovskite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 32 publications
4
89
0
Order By: Relevance
“…The bulk YMnO 3 is FE with the Curie temperature T CE = 570-990 K and AFM with the Néel temperature T N = 70-130 K [67]. It was shown that the strained hexagonal YMnO 3 can be stabilized in orthorhombic perovskite phase, which is an excellent example for strain engineering [68]. Strain has been found to be crucial in stabilizing other RMnO 3 in the FE hexagonal form [18].…”
Section: (D) Thin Filmsmentioning
confidence: 99%
“…The bulk YMnO 3 is FE with the Curie temperature T CE = 570-990 K and AFM with the Néel temperature T N = 70-130 K [67]. It was shown that the strained hexagonal YMnO 3 can be stabilized in orthorhombic perovskite phase, which is an excellent example for strain engineering [68]. Strain has been found to be crucial in stabilizing other RMnO 3 in the FE hexagonal form [18].…”
Section: (D) Thin Filmsmentioning
confidence: 99%
“…This phase can be also stabilized in YMO thin films under compressive epitaxial stress. [8][9][10] Whereas the phase stabilization is documented in these references, the physical properties of orthorhombic YMO films are not reported.…”
Section: Introductionmentioning
confidence: 99%
“…This phase can be also stabilized in YMO thin films under compressive epitaxial stress. [8][9][10] Whereas the phase stabilization is documented in these references, the physical properties of orthorhombic YMO films are not reported.We report here on the growth and magnetic characterization of AF perosvkite YMO thin films. Epitaxial films were deposited on SrTiO 3 ͑STO͒ substrates having different orientations; we will show that this strategy allows selection of the YMO crystal out-of-plane orientation.…”
mentioning
confidence: 99%
“…For example, doping (Ba,Ca)TiO 3 FE ceramics and the incipient FE SrTiO 3 with tin resulted in the enhancement [28][29][30][31] Modern epitaxial engineering techniques can stabilize metastable structures through artificial elastic boundary conditions (misfit strain) and/or rate-limited kinetics. 38 Therefore, they offer an alternative approach to avoid the restrictions imposed by bulk thermodynamics in order to grow novel materials with enhanced properties that have the potential to replace PZT in a variety of technological applications. A recent attempt to synthesize SnTiO 3 films on sapphire and perovskite substrates from ceramic SnO 2 and TiO 2 targets utilizing PLD produced nonpolar ilmenite-type structures with only traces of a second phase compatible with perovskite geometry.…”
Section: Introductionmentioning
confidence: 99%